Silver single atoms and nanoparticles on floatable monolithic photocatalysts for synergistic solar water disinfection - Jian Wang; Jiahe Zhang; Yang Li; Xinghui Xia; Hengjing Yang; Jae-Hong Kim; Wen Zhang (Nature Communications)
Abstract Photocatalytic water disinfection technology is highly promising in off-grid areas due to abundant year-round solar irradiance. However, the practical use of powdered photocatalysts is impeded by limited recovery and inefficient inactivation of stress-resistant bacteria in oligotrophic surface water. Here we prepare a floatable monolithic photocatalyst with ZIF-8-NH2 loaded Ag single atoms and nanoparticles (AgSA+NP/ZIF). Atomically dispersed Ag sites form an Ag−N charge bridge, extending the lifetime of charge carriers and thereby promoting reactive oxygen species (ROS) generation. The photothermal effect of the plasmonic Ag nanoparticles reduces the bacterial resistance to ROS and impairs DNA repair capabilities. Under sunlight irradiation, the synergistic effect of Ag single atoms and nanoparticles enables 4.0 cm2 AgSA+NP/ZIF to achieve over 6.0 log inactivation (99.9999%) for the stress-resistant Escherichia coli (E. coli) in oligotrophic surface water within 30 min. Furthermore, 36 cm2 AgSA+NP/ZIF is capable of disinfecting at least 10.0 L of surface water, which meets the World Health Organization (WHO) recommended daily per capita drinking water allocation (8.0 L). This study presents a decentralized and sustainable approach for water disinfection in off-grid areas.